INCIDENCE AND CHARACTERISTICS OF CORONARY ARTERY ECTASIA IN PATIENTS UNDERGOING CORONARY ANGIOGRAPHY AT ARMY CARDIAC CENTER LAHORE - Shafiq, Faisal; Usman, Ahmad; Sultan, Mehboob; Shehzad, Khurram; Haroon, Namra; ., Osama (Pakistan Armed Forces Medical Journal, 2021)
Objective: To estimate the incidence and characteristics of coronary artery ectasia in patients undergoing coronary angiography.Study Design: A prospective analysis.Place and Duration of Study: This study was conducted at Army Cardiac Center, Lahore over a period of two years from Jan 2018 to Dec 2019.Methodology: Its prospective analysis of all coronary angiograms performed in our catheterization laboratory during study period. Markis classification was the basis to define and classify coronary artery ectasia. Demographical, clinical, and laboratory data were collected for each patient in this study.Results: A total of 172 (3.9%) out of 4,372 coronary angiograms showed coronary artery ectasia. Among coronary artery ectasia group, mean age 58 ± 10 years, 90% were male, 47% were current smokers, 32% were hypertensive, 15% had diabetes Mellitus and 37% had dyslipidemia. The most common clinical presentation was Non STsegment elevation myocardial infarction (31%), followed by Stable ischemic heart disease in 28%. Right coronary artery was the most frequent coronary artery involved (57%) while Markis Class 3 pattern was seen as most common type of coronary artery ectasia.Conclusion: The frequency of coronary artery ectasia among our patients undergoing coronary angiography was about 4%. Right coronary artery remained the most common affected artery.